PENGARUH RASIO PAJAK TANGGUHAN, KEAHLIAN PAJAK, DAN REMUNERASI TERHADAP PENGHINDARAN PAJAK (Studi Empiris pada Perusahaan Publik yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2017) - Melinda Regita Cahyani; Endang Kiswara (Diponegoro Journal of Accounting, 2019)
This study aims to examine the influence of deferred tax ratio, the tax expertise, and the performance-based remuneration of it’s key management personnel on the relationship on tax avoidance. In this study, tax avoidance was measured using a ratio scale through the book tax differences. The deferred tax ratio and the tax expertise were measured using the interval scale, whereas in previous study was using the nominal scale (dummy variable). While the performance-based remuneration was measured through the ratio scale. The control variables used in this study are size, ROA, board independence, and CEO tenure. The population used in this study are companies listed on the Indonesia Stock Exchange (IDX) for the period 2015-2017 using the random sampling method. The final sample obtained was 135 companies out of a total of 476 companies during 2015-2017. Hypothesis testing is done using panel data regression analysis.The results of this study show that the deferred tax ratio have a positive effect on tax avoidance. Similarly, the tax expertise have a positive effect on corporate tax avoidance. While the performance-based remuneration of it’s key management personnel are not affected by tax avoidance.